IMPLEMENTASI KETENTUAN MASA IDDAH WANITA MENOPAUSE DI KABUPATEN KEDIRI - Shodiqin, Mohammad (IAIN BONE, 2024)
Surah At-Thalaq verse 4 explains the iddah period for divorced women. However, the conception of the iddah period for menopausal women still prevails among the society. This research is focused on understanding the community's understanding of the conception of the iddah period for menopausal women in Surah At-Thalaq verse 4. Interviews are the primary means of data gathering in this qualitative approach. The results showed that people's understanding of the conception of the iddah period for menopausal women in Surah At-Thalaq verse 4 is still limited and sometimes misunderstood. Some respondents think that the iddah period for menopausal women is not needed because they cannot get pregnant anymore. However, additionally there are those who argue that the iddah period is still needed because it is a religious provision that must be followed. Therefore, there needs to be better socialization and education regarding the conception of the iddah period for menopausal women in Surah At-Thalaq verse 4 so that people can understand and practice it correctly.